The Safety and Tolerability of Linezolid in Novel Short-Course Regimens Containing Bedaquiline, Pretomanid, and Linezolid to Treat Rifampicin-Resistant Tuberculosis: An Individual Patient Data Meta-analysis - Hasan, Tasnim; Medcalf, Ellie; Nyang'wa, Bern-Thomas; Egizi, Erica; Berry, Catherine; Dodd, Matthew; Foraida, Salah; Gegia, Medea; Li, Mengchun; Mirzayev, Fuad; Morgan, Hannah; Motta, Ilaria; et al. (Clinical infectious diseases, 2024)
Abstract Background Effectiveness, safety, tolerability, and adherence are critical considerations in shifting to shorter tuberculosis (TB) regimens. Novel 6-month oral regimens that include bedaquiline (B), pretomanid (Pa), and linezolid (L), with or without a fourth drug, have been shown to be as or more effective than the established longer regimens for the treatment of multidrug-resistant/rifampicin-resistant TB (MDR/RR-TB). We aimed to evaluate the safety and tolerability of linezolid in BPaL-containing regimens for the treatment of MDR/RR-TB among recently completed clinical trials. Methods A review and meta-analysis was undertaken including published and unpublished data from clinical trials, conducted between 2010 and 2021, that evaluated regimens containing BPaL for the treatment of MDR/RR-TB. Individual patient data were obtained. For each BPaL-containing regimen, we evaluated the frequency and severity of treatment-related adverse events. The risk difference of adverse events for each regimen was calculated, in comparison to patients assigned to receiving the lowest cumulative exposure of linezolid. Results Data from 3 clinical trials investigating 8 unique BPaL-containing regimens were included, comprising a total of 591 participants. Adverse events were more frequent in groups randomized to a higher cumulative linezolid dose. Among patients who were randomized to a daily dose of 1200 mg linezolid, 68 of 195 (35%) experienced a grade 3–4 adverse event versus 89 of 396 (22%) patients receiving BPaL-containing regimens containing 600 mg linezolid. Conclusions Regimens containing BPaL were relatively well tolerated when they included a daily linezolid dose of 600 mg. These novel regimens promise to improve the tolerability of treatment for MDR/RR-TB. Different bedaquiline, pretomanid, and linezolid–containing regimens from recently published clinical trials for the treatment of drug-resistant tuberculosis are compared. Different linezolid doses and durations were used in these regimens, allowing for an assessment of the safety of linezolid.